Effects of conditioned social fear on ethanol drinking and vice-versa in male mice - Kornhuber, Johannes; Huber, Sabine; Zoicas, Iulia (Psychopharmacology, 2019)
Rationale: Social anxiety disorder (SAD) is highly comorbid with alcohol use disorders, but the complex relationship between social fear and alcohol drinking is poorly understood due to the lack of specific animal models. Objectives: We investigated whether social fear alters ethanol drinking under both stress-free and stress-inducing conditions and whether ethanol alleviates symptoms of social fear. Methods: We used the social fear conditioning (SFC) paradigm, an animal model with face and predictive validity to SAD, to induce specific social fear in male CD1 mice, i.e., without comorbid depression or anxiety-like behavior. Plasma corticosterone (CORT) levels were measured in conditioned (SFC+) and unconditioned (SFC−) mice after exposure to non-social or social stimuli. Ethanol drinking was assessed in the two-bottle free-choice paradigm (1) for 16 days under stress-free conditions and (2) for 6 h after exposure to social stimuli. The effects of ethanol drinking and social fear on anxiety-like behavior and taste preference were tested in the elevated plus-maze and sucrose and quinine preference tests. Results: We show that exposure to social but not non-social stimuli leads to higher plasma CORT levels in SFC+ compared with SFC− mice. We also show that social fear decreases voluntary ethanol consumption under stress-free conditions, but increases ethanol consumption after exposure to social stimuli. Ethanol drinking, on the other hand, reduces social fear without altering anxiety-like behavior, locomotor activity, and taste preference. Conclusions: These results have important clinical connotations as they suggest that voluntary ethanol drinking might specifically reverse symptoms of social fear in a SAD-relevant animal model.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Anxiety; CORT ELISA; Corticosterone; Ethanol drinking; Extinction; Locomotion; Social fear conditioning; Social investigation; Taste preference